2020
DOI: 10.17267/2317-3378rec.v9i1.2581
|View full text |Cite
|
Sign up to set email alerts
|

Perfil do câncer infantil em um estado da Amazônia Ocidental em 2018

Abstract: OBJETIVO: Identificar o perfil do câncer infantil em um estado da Amazônia Ocidental em 2018. MATERIAIS E MÉTODO: Trata-se de um estudo transversal, exploratório e descritivo, realizado na unidade de assistência de alta complexidade de um hospital de grande porte do Acre. A população de estudo foi formada por 49 crianças de 0 a 10 anos com diagnóstico de câncer e atendidas no local de estudo no ano de 2018. RESULTADOS: Os dados apontam que a maioria das crianças (38,8%), encontrava-se na faixa etária e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…18 Thus, leukemias are the most common hematologic neoplasms among children and adolescents, being more present in children under 5 years of age. 19 The study shows a greater predominance of individuals with brown skin color, being in agreement with studies developed in the state of Piauí 20 , Alagoas 13 , Minas Gerais 14 , and Acre 15 . Research developed in the South region observed white individuals as the most affected by childhood and adolescent cancer.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…18 Thus, leukemias are the most common hematologic neoplasms among children and adolescents, being more present in children under 5 years of age. 19 The study shows a greater predominance of individuals with brown skin color, being in agreement with studies developed in the state of Piauí 20 , Alagoas 13 , Minas Gerais 14 , and Acre 15 . Research developed in the South region observed white individuals as the most affected by childhood and adolescent cancer.…”
Section: Discussionsupporting
confidence: 83%
“…1 Male predominance was observed in this study and in another study involving children and adolescents, which covered the entire Brazilian territory 9 and isolated studies directed at states in different regions of the country. 4,[12][13][14][15][16] Males are more likely to have congenital diseases (chromosomal anomalies, monogenic syndromes, and nonsyndromic birth defects), which is associated with the risk of childhood cancers. 18 A higher number of records were found in the 0 to 4 years age group, corroborating a national study 9 and from different Brazilian states, 4,13,[15][16]18 as well as an international study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…É oportuno reforçar que o conhecimento técnico-científico da enfermeira é imprescindível no cuidado junto ao cliente com câncer, de modo a agir com segurança diante das situações que se lhes apresentam e nas quais precisa estar apta a atuar. Contudo, há de se valorizar e tomar consciência de, por detrás de uma doença crônica, dos sinais e sintomas clínicos dela decorrente e dos efeitos adversos dos fármacos utilizados no seu combate, existe um ser humano dotado de emoções, valores, crenças, modos de ser e de viver singulares que, muitas vezes, determinam ou influenciam as ações e reações frente a doença e seu tratamento 26 .…”
Section: Reconhecendo Os Desafios Do Tratamento Do Enfermeiro Na Onco...unclassified